Transitioning from Traditional to AI-Based Educational Assessment in Nigeria: Prospects and Challenges - Isunueo, B. O.; Oni, M. B. (Journal of Research in Adult and Continuing Education, 2025)
This paper explores the potentials of artificial intelligence (AI) to transform educational assessment in Nigeria system historically challenged by inconsistency, lack of students’ feedback, bureaucracy, and examination malpractices. Drawing on secondary literature and employing the AI-Ethical Assessment Transformation (AI-EAT) Model, the paper conceptualizes assessment reform as a process mediated by AI innovations that enhances validity, reliability, and efficiency, and ethical and policy enablers promote fairness, accountability, and inclusiveness. The paper espoused that automated scoring of essays, adaptive testing, and learning analytics have the potential to raise the level of objectivity and individualized feedback, yet such initiatives are doomed to fail in the case of weak governance frameworks covering the problem of data privacy, algorithm bias, and inequality in access. The educational measurement theory, sociotechnical systems theory and algorithmic governance ethics to depict that the combination of technological innovation, institutional preparedness and ethical control is needed in order to achieve sustainable AI use in assessment and evaluation in Nigeria’s educational system were incorporated. Thus, it is concluded that an inclusive policy designed to align with the international standards of transparency and educational equity is critical for effective AI integration in assessment practices.